Remote sensing of Qatar nearshore habitats with perspectives for coastal management. Issue 2 (30th April 2016) - Warren, Christopher; Dupont, Jennifer; Abdel-Moati, Mohamed; Hobeichi, Sanaa; Palandro, David; Purkis, Sam
Abstract: A framework is proposed for utilizing remote sensing and ground-truthing field data to map benthic habitats in the State of Qatar, with potential application across the Arabian Gulf. Ideally the methodology can be applied to optimize the efficiency and effectiveness of mapping the nearshore environment to identify sensitive habitats, monitor for change, and assist in management decisions. The framework is applied to a case study for northeastern Qatar with a key focus on identifying high sensitivity coral habitat. The study helps confirm the presence of known coral and provides detail on a region in the area of interest where corals have not been previously mapped. Challenges for the remote sensing methodology associated with natural heterogeneity of the physical and biological environment are addressed. Recommendations on the application of this approach to coastal environmental risk assessment and management planning are discussed as well as future opportunities for improvement of the framework. Highlights: Application of remote sensing framework to map Qatar coral habitats Maps confirm the presence of known coral and reveal coral areas not previously mapped. Natural heterogeneity of the physical and biological environment presents challenges. Perspectives provided on applying results to coastal risk assessment and management